2016
DOI: 10.1021/acs.jpcc.5b12559
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of 2,4-Dichlorophenoxyacetic Acid to Catalase Immobilized on Hierarchical Porous Calcium Phosphate: Kinetic Aspect and Electrochemical Biosensor Construction

Abstract: The inhibition mechanism of 2,4-dichlorophenoxyacetic acid (2,4-D) to catalase was studied by a catalase biosensor in a flow-injection analysis (FIA) system. This system provides an ideal sensing platform to electrochemically evaluate the chemical mechanism of enzyme inhibition. Hierarchical porous calcium phosphate (hp-CaP), as a biocompatible nanomaterial, was used to immobilize catalase for repeat use. 2,4-D together with H 2 O 2 was injected into the bioreactor of the immobilized catalase-FIA system during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Industrial applications for catalase include removal of hydrogen peroxide after cold sterilization steps in food processing (Farkye, 2004;Lee, 2004;Tarhan, 1995). Catalase has also been used in the manufacturing of semi-conductors (Akyilmaz and Kozgus, 2009;Liu et al 2016) and in the textile industry (Arabaci and Usluoglu, 2013;Costa et al 2002). Moreover, catalase is indispensable for carrying out biotransformation processes with the use of oxidases to cause decomposition of hydrogen…”
Section: Introductionmentioning
confidence: 99%
“…Industrial applications for catalase include removal of hydrogen peroxide after cold sterilization steps in food processing (Farkye, 2004;Lee, 2004;Tarhan, 1995). Catalase has also been used in the manufacturing of semi-conductors (Akyilmaz and Kozgus, 2009;Liu et al 2016) and in the textile industry (Arabaci and Usluoglu, 2013;Costa et al 2002). Moreover, catalase is indispensable for carrying out biotransformation processes with the use of oxidases to cause decomposition of hydrogen…”
Section: Introductionmentioning
confidence: 99%
“…2 It is also found as an active ingredient in many pesticides, and improper usage may prove fatal to human health even at trace amounts as it leads to excess release of reactive oxygen species. 5 Overuse of this herbicide has also led to its persistence in water sources due to its high solubility and nonbiodegradable nature. 1,6 Even a concentration less than 3 mg L −1 in drinking water imparts an unpleasant taste and odor.…”
Section: Introductionmentioning
confidence: 99%
“…2,4-Dichlorophenoxyacetic acid (2,4-D) is an auxin-like herbicide used conventionally for controlling growth of broad-leaf weeds in agricultural fields. 2,4-D mimics the action of auxin (a plant growth hormone) and induces uncontrolled growth and death of weeds . It is also found as an active ingredient in many pesticides, and improper usage may prove fatal to human health even at trace amounts as it leads to excess release of reactive oxygen species . Overuse of this herbicide has also led to its persistence in water sources due to its high solubility and nonbiodegradable nature. , Even a concentration less than 3 mg L –1 in drinking water imparts an unpleasant taste and odor .…”
Section: Introductionmentioning
confidence: 99%
“…Alkaline phosphatase (ALP) immobilized on sol-gel/chitosan film on carbon paste electrodes was used to detect these herbicides in the presence of heavy metals based on the inhibition of ascorbic acid 2-phosphate hydrolysis [15]. More recently, Lui et al reported the inhibition mechanism of 2,4-D to catalase supported on porous calcium phosphate and the construction of a biosensor based on a flow-injection analysis system to detect 2,4-D in commercial bean sprouts samples [16].…”
Section: Introductionmentioning
confidence: 99%